2013
DOI: 10.1083/jcb.201301148
|View full text |Cite
|
Sign up to set email alerts
|

The STIM1 CTID domain determines access of SARAF to SOAR to regulate Orai1 channel function

Abstract: Two distinct lobes in the C-terminal inhibitory domain in STIM1 determine access of the inhibitor SARAF to the activating SOAR domain to regulate the slow Ca2+-dependent inactivation of Orai1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
163
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(178 citation statements)
references
References 28 publications
14
163
1
Order By: Relevance
“…This process leaves a "STIM1-free" but partially active Orai1 P245L that contributes to the measured current and therefore to an apparent reduction of the slow inactivation process. Two other mutants, G98S and L138F, which have also been associated with tubular aggregate myopathy and congenital miosis syndromes [65], share the defect that we identified in P245L of constitutive channel opening [43,53,65]. Although the constitutive conductance of Orai1 P245L may be less pronounced in heterozygous patients than in heterologous overexpression experiments due to formation of mutant and WT heteromultimers, based on results presented here and on previous findings, we propose that STIM1-independent constitutive channel activation of Orai1 channels is likely the common factor that underlies the disease state.…”
Section: How Mutation In the Tm4 Proline Bend Might Induce Myopathymentioning
confidence: 99%
“…This process leaves a "STIM1-free" but partially active Orai1 P245L that contributes to the measured current and therefore to an apparent reduction of the slow inactivation process. Two other mutants, G98S and L138F, which have also been associated with tubular aggregate myopathy and congenital miosis syndromes [65], share the defect that we identified in P245L of constitutive channel opening [43,53,65]. Although the constitutive conductance of Orai1 P245L may be less pronounced in heterozygous patients than in heterologous overexpression experiments due to formation of mutant and WT heteromultimers, based on results presented here and on previous findings, we propose that STIM1-independent constitutive channel activation of Orai1 channels is likely the common factor that underlies the disease state.…”
Section: How Mutation In the Tm4 Proline Bend Might Induce Myopathymentioning
confidence: 99%
“…Furthermore, SARAF has been reported to modulate cytosolic and ER Ca 2ϩ concentration (8). The activation of SARAF requires the intraluminal (N-terminal) region, while the interaction with SARAF involves the cytosolic region, which interacts with the C-terminal inhibitory domain of STIM1 (downstream the STIM1 Orai1 activation region (SOAR)) to regulate the STIM1/ Orai1 interaction (9). SARAF is associated with STIM1 under resting conditions and translocates to ER-PM regions in a STIM1-dependent manner (8).…”
mentioning
confidence: 99%
“…Deletion of the CTID region has been reported to induce spontaneous clustering of STIM1 and activation of CRAC channels independently of Ca 2C store depletion. 5 Studies performed in Muallems lab revealed that SARAF is associated to STIM1 at rest and Ca 2C store depletion results in a initial dissociation followed by re-interaction of both proteins. 5 Recently, we have reported that maximal dissociation occurs after 30 s of the initiation of store depletion by treatment with TG, and full re-association is achieved 30 s later.…”
Section: Introductionmentioning
confidence: 99%
“…5 Studies performed in Muallems lab revealed that SARAF is associated to STIM1 at rest and Ca 2C store depletion results in a initial dissociation followed by re-interaction of both proteins. 5 Recently, we have reported that maximal dissociation occurs after 30 s of the initiation of store depletion by treatment with TG, and full re-association is achieved 30 s later. 6 In parallel, we have observed a reciprocal interaction of SARAF with Orai1 that might be aimed to enhanced Orai1 channel function as determined in NG115-401L cells lacking a significant expression of STIM1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation